GE_GERICHTE P/7346/2015 vom 25. September 2018 - GE Cour de justice (2018)
FRAIS DE LA PROCÉDURE ; INDEMNITÉ(EN GÉNÉRAL) ; POURSUITE PAR VOIE DE FAILLITE ; CONSEIL D'ADMINISTRATION | CPP.426; CPP.429.al1.leta; CO.716